Mechanisms of flat weaving technology - Choogin, Valeriy V., author; Bandara, Palitha; Chepelyuk, Elena, author; Textile Institute (Manchester, England) (Oxford ; Philadelphia : Woodhead Publishing Ltd in association with the Textile Institute, 2013)
Includes bibliographical references and index